Barriers to HIV Medication Adherence as a Function of Regimen Simplification. Issue 1 (10th August 2016) - Chen, Yiyun; Chen, Kun; Kalichman, Seth C.
Abstract: Background: Barriers to HIV medication adherence may differ by levels of dosing schedules. Purpose: The current study examined adherence barriers associated with medication regimen complexity and simplification. Methods: A total of 755 people living with HIV currently taking anti-retroviral therapy were recruited from community services in Atlanta, Georgia. Participants completed audio-computer-assisted self-interviews that assessed demographic and behavioral characteristics, provided their HIV viral load obtained from their health care provider, and completed unannounced phone-based pill counts to monitor medication adherence over 1 month. Results: Participants taking a single-tablet regimen (STR) were more likely to be adherent than those taking multi-tablets in a single-dose regimen (single-dose MTR) and those taking multi-tablets in a multi-dose regimen (multi-dose MTR), with no difference between the latter two. Regarding barriers to adherence, individuals taking STR were least likely to report scheduling issues and confusion as reasons for missing doses, but they were equally likely to report multiple lifestyle and logistical barriers to adherence. Conclusions: Adherence interventions may need tailoring to address barriers that are specific to dosing regimens.